Muhammadiyah Asset Management Information System (SIMAM) In Regional Leaders Of Muhammadiyah Banyuwangi - Adawiyah, Putri Robiatul; Jatmiko, Hadi (Journal Of Humanities Community Empowerment, 2024)
This Community Service aims to assist with the administration of the Inventory of Waqf Assets and Property Through the Implementation of the Muhammadiyah Asset Management Information System (SIMAM) at the Muhammadiyah Banyuwangi Regional Leadership. This service activity departs from Partner Problem Identification, namely: 1). Banyuwangi PDM Partners are still not in order in the administration of assets and property, 2). Muhammadiyah Banyuwangi Regional Leaders have Branch and Twig Leaders spread across Banyuwangi Regency and have assets in all fields. However, the data collection that has been carried out since 2020 has been constrained by various problems, both internal problems with limited implementing resources, 3). Data and archived copies of documents that are recorded in the PDM database of the total assets are still very low at 2%; 4). External problems arose, namely in the civil field administrative issues such as permits for the construction of da'wah centers in several locations and the emergence of the threat of da'wah terror in several Muhammadiyah Banyuwangi charities; 5). Lack of orderly administration in the field of data collection and archiving of assets and property owned by leaders from branches to regions; 6). SIMAM accounts and passwords provided during training by East Java PWM while in Malang need to be reset again and further coordinate technical implementation with regional level admins; 7) The emergence of problems at certain point locations such as conflicts in the Tampo, Sraten, and Cluring areas which drained time and made leaders less focused on advocacy assistance on orderly administrative activities which must be prioritized. The objectives of this Community Service Activity are: 1). Assistance in Inventory of Waqf Assets and Land for the Muhammadiyah organization at PDM Banyuwangi; 2). Synchronizing the program between the Waqf and Property Assembly with the Waqf strategic plan, ZIS (Zakat, Infaq, and Sadaqah), and Economic Empowerment 3). PDM Banyuwangi has an organized, safe, systematic and accountable asset and property information system manager; 4) Improving the quality of waqf management and the movement for certifying waqf lands within the Organization. 5) Improving ZIS management and developing cash and productive forms of waqf.